Efficacy and Safety of a Novel Gummy Formulation for the Management of Cough in Adults: Double Blind, Randomized, Placebo-Controlled Trial - Domenico Leonardo Grasso; Kiran Narayanappa; Rosario Russo (Applied Sciences, 2022)
The cough is one of the most common medical complaints affecting the general population. It is well known that persisting cough negatively affects subjects’ quality of life (QoL) and sleep quality. The aim of the current double blind, randomized, placebo-controlled, pilot study was to assess the effectiveness of a novel medical device in gummy format in reducing cough and improving QoL in adult subjects with acute persisting cough. Forty subjects were enrolled and randomized into two arms according to the treatment. Both the investigational product (IP) and placebo were administered orally, three times per day for 10 consecutive days. Cough symptoms and severity were measured by the Cough Clinical Score (CCS) consisting of a 6-point Likert scale, Leicester Cough Questionnaire (LCQ) and cough severity visual analogue scale (VAS). QoL was rated using the SF-36 (short form) questionnaire. Significant improvements were seen both in the daytime and nighttime cough score after 5 days and at the end of treatment in the IP group but not in those subjects taking the placebo. QoL and sleep disturbances were ameliorated significantly in the IP group only. In conclusion, IP was found safe, well-tolerated and effective in the management of persisting cough in adults.